Comparative Transcriptomic Analyses of Differentially Expressed Genes in Transgenic Melatonin Biosynthesis Ovine HIOMT Gene in Switchgrass - Yuan, Shan; Guan, Cong; Liu, Sijia; Huang, Yanhua; Tian, Danyang; Cui, Xin; Zhang, Yunwei; Yang, Fuyu (Frontiers in Plant Science, 2016)
Melatonin serves pleiotropic functions in prompting plant growth and resistance to various stresses. The accurate biosynthetic pathway of melatonin remains elusive in plant species, while the N-acetyltransferase and O-methyltransferase were considered to be the last two key enzymes during its biosynthesis. To investigate the biosynthesis and metabolic pathway of melatonin in plants, the RNA-seq profile of overexpression of the ovine HIOMT was analyzed and compared with the previous transcriptome of transgenic oAANAT gene in switchgrass, a model plant for cellulosic ethanol production. A total of 946, 405, and 807 differentially expressed unigenes were observed in AANAT vs. control, HIOMT vs. control, and AANAT vs. HIOMT, respectively. Two hundred and seventy-five upregulated and 130 downregulated unigenes were detected in transgenic oHIOMT line comparing with control, including the significantly upregulated (F-box/kelch-repeat protein, zinc finger BED domain-containing protein-3) genes, which were potentially correlated with enhanced phenotypes of shoot, stem and root growth in transgenic oHIOMT switchgrass. Several stress resistant related genes (SPX domain-containing membrane protein, copper transporter 1, late blight resistance protein homolog R1A-6 OS etc.) were specifically and significantly upregulated in transgenic oHIOMT only, while metabolism-related genes (phenylalanine-4-hydroxylase, tyrosine decarboxylase 1, protein disulfide-isomerase and galactinol synthase 2 etc.) were significantly upregulated in transgenic oAANAT only. These results provide new sights into the biosynthetic and physiological functional networks of melatonin in plants.